'To the left, to the right': Representing conservative women's interests. (July 2015) - Campbell, Rosie; Childs, Sarah
The study of conservative women is expanding to compensate for the historic over-emphasis of gender and politics research on left-wing women. We add to this burgeoning literature and assess the extent to which the modern gender gap in political attitudes – where women have moved to the left of men – is evident among supporters of the British Conservative Party. We find that, like women party members, women Conservative supporters are noticeably to the left of men, but only on economic issues. This sex gap cannot simply be accounted for by women's employment in the public sphere, lesser interest in politics or because they are more morally conservative than male Conservatives. These findings are likely to have serious implications for intra-party discipline, the support for the Conservative Party at the next British general election and, if replicated elsewhere, speak to what it means to 'represent' the interests of right-wing women.